The Free Market Experiment in Latin America: Moving Beyond Past Policies to Search for a Pathway Forward. Issue 2 (June 2014) - Pineo, Ronn
This article examines the performance of neoliberal economic policies in Latin America over the last several decades. Scrutiny is given to growth, development, inequality, poverty, and social concerns. Recent evidence is brought to bear in evaluating the efficacy of neoliberalism with respect to these matters. Following the work of Henry Bruton, the article offers a reconsideration of the conventional critique of prior import substitution industrial policies. Finally, building upon a wide array of recent works in economic developmental theory, the article puts forward some policy recommendations for promotion of economic development in Latin America.